2013
DOI: 10.1089/jamp.2011.0952
|View full text |Cite
|
Sign up to set email alerts
|

Comparative In Vitro Performance of Three Small-Volume Valved Holding Chambers with Beclomethasone/Formoterol Pressurized Metered Dose Inhaler

Abstract: The Vortex and the ACP VHCs present interesting advantages over the AS VHC to be used with Innovair pMDI. However, these results are based on an in vitro evaluation and need to be validated in an in vivo study in order to clinically assess the performance of these VHCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…30 Similar results were reported in other studies of salbutamol and beclomethasone/formoterol pMDIs. 51 , 52 Importantly, where a 2 s delay in sampling was imposed for the AC+FV aVHC, simulating use by a more representative semi-coordinated patient, the FPD remained similar to that via a pMDI coordinated perfectly (FPD ratio approximately 85–120%). 30…”
Section: Resultsmentioning
confidence: 99%
“…30 Similar results were reported in other studies of salbutamol and beclomethasone/formoterol pMDIs. 51 , 52 Importantly, where a 2 s delay in sampling was imposed for the AC+FV aVHC, simulating use by a more representative semi-coordinated patient, the FPD remained similar to that via a pMDI coordinated perfectly (FPD ratio approximately 85–120%). 30…”
Section: Resultsmentioning
confidence: 99%
“…23 Several previous studies have reported similar results, namely that the accessory device significantly increased the relative lung bioavailability compared to the pMDI alone (P Ͻ .01). 10,22,24,25 This may be because inhalation from an accessory device decreases the velocity of the aerosol particles and allows some evaporation of the propellant, thereby decreasing the particle size and the quantity of salbutamol deposited in the patient's mouth and throat (represented by the induction port of the Andersen MKII cascade impactor in this study). 22 When using the pMDI without an accessory device, the majority of the emitted dose was deposited in the induction port, but when using the accessory devices, the majority of the emitted dose was deposited in the accessory device.…”
Section: Discussionmentioning
confidence: 96%
“…9 Most traditional accessory devices on the market are made from lightweight plastic for greater durability and enhanced device portability. 10,11 Polypropylene and polycarbonate are the most commonly used materials for making plastic spacers or valved holding chambers; however, their non-conducting nature encourages electrostatic charges within the device. [12][13][14] Because drugs released from pMDIs also are electrically charged, electrostatic reactions inevitably occur between the charged walls of the accessory device and the emitted drug.…”
Section: Introductionmentioning
confidence: 99%
“…There are few substantial studies that estimate the magnitude and clinical impact of these effects in real life [ 58 ]: most of these address the effects of spacers/VHCs on the bronchodilatation produced by short-acting β-agonists (and do suggest a measurable effect, even in patients with good pMDI technique) [ 50 , 59 ], although some address the effects of inhaled corticosteroids. Devices made of antistatic materials further increase the delivery of the respirable particle fraction [ 46 , 51 , 52 , 60 ], although again the effects are sometimes marginal [ 55 , 56 , 61 ], and the clinical consequences of this for real-life disease control are unclear.…”
Section: Assessing the Potential Impact Of Spacers/vhcs On Drug Delivmentioning
confidence: 99%